Comparison of Akt Expression in the Cerebrum and Cerebellum of Newborn Mus musculus Exposed to Physical Stress and Psychological Stress During Pregnancy - Herlina Puji Angesti; Hermanto Tri Joewono; Widjiati (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Prenatal stress prevalence is almost half of the population of pregnant women worldwide.Stress will stimulate glucocorticoids which can disrupt the PI3K-Akt cascade. PI3K-Akt deficiency willcause impaired fetal brain growth and development.Objective: To compare the Akt expression in the cerebrum and cerebellum of newborn Mus musculusexposed to physical stress, psychological stress, the combination of psychological and physical stress, andwithout stress exposure. Method: This study was experimental laboratory research. Twenty-four female mice were used as samplesand divided into four groups: physical stress exposure group, psychological stress exposure group, thecombination of psychological and physical stress exposure group, and control group. Akt expression wastested by immunohistochemistry (IHC) staining. Statistical analysis used the One Way Anova and KruskalWallis test.